Role of Toxoplasma gondii Chloroquine Resistance Transporter in Bradyzoite Viability and Digestive Vacuole Maintenance - Geetha Kannan (American Society for Microbiology, 2019)
ABSTRACT Toxoplasma gondii is a ubiquitous pathogen that can cause encephalitis, congenital defects, and ocular disease. T. gondii has also been implicated as a risk factor for mental illness in humans. The parasite persists in the brain as slow-growing bradyzoites contained within intracellular cysts. No treatments exist to eliminate this form of parasite. Although proteolytic degradation within the parasite lysosome-like vacuolar compartment (VAC) is critical for bradyzoite viability, whether other aspects of the VAC are important for parasite persistence remains unknown. An ortholog of Plasmodium falciparum chloroquine resistance transporter (CRT), TgCRT, has previously been identified in T. gondii. To interrogate the function of TgCRT in chronic-stage bradyzoites and its role in persistence, we knocked out TgCRT in a cystogenic strain and assessed VAC size, VAC digestion of host-derived proteins and parasite autophagosomes, and the viability of in vitro and in vivo bradyzoites. We found that whereas parasites deficient in TgCRT exhibit normal digestion within the VAC, they display a markedly distended VAC and their viability is compromised both in vitro and in vivo. Interestingly, impairing VAC proteolysis in TgCRT-deficient bradyzoites restored VAC size, consistent with a role for TgCRT as a transporter of products of digestion from the VAC. In conjunction with earlier studies, our current findings suggest a functional link between TgCRT and VAC proteolysis. This study provides further evidence of a crucial role for the VAC in bradyzoite persistence and a new potential VAC target to abate chronic Toxoplasma infection. IMPORTANCE Individuals chronically infected with the intracellular parasite Toxoplasma gondii are at risk of experiencing reactivated disease that can result in progressive loss of vision. No effective treatments exist for chronic toxoplasmosis due in part to a poor understanding of the biology underlying chronic infection and a lack of well-validated potential targets. We show here that a T. gondii transporter is functionally linked to protein digestion within the parasite lysosome-like organelle and that this transporter is necessary to sustain chronic infection in culture and in experimentally infected mice. Ablating the transporter results in severe bloating of the lysosome-like organelle. Together with earlier work, this study suggests the parasite’s lysosome-like organelle is vital for parasite survival, thus rendering it a potential target for diminishing infection and reducing the risk of reactivated disease.